Analysis of Chinese Core Literatures on Protective Clothing Research (Journal of Fiber Bioengineering and Informatics, 2023)
Protective clothing research is booming worldwide and has become a hotspot in academia. This paper compares the literature in Chinese Core Journals with international journals on protective clothing researches to provide framework for future study. By using the system of CiteSpace, the literatures on protective clothing were selected from CNKI and WOS databases, and knowledge visualization analysis was conducted in terms of the number of articles, clustering graph, time zone view, emergent words, timeline, etc.. The commonalities and differences between literature in Chinese Core Journals with those in international one are discussed, and the achievements in protective clothing research are summarize to providing new research perspectives. It is found that the research themes in both Chinese literature and international literature have changed in response to the social and natural environment, and the research topics on protective clothing are constantly new on the basis of the previous period; the research themes of Chinese literature focus on "emergency rescue", "thermal protection", "public safety" and "medical treatment", while the themes of international literature focus on "textile", "composite", "mechanical property", "antibacterial" and "nanoparticle".